Perlindungan Hukum Nasabah PT Asuransi Jiwa Kresna Atas Gagal Bayar Ditinjau Dari Undang-Undang Nomor 21 Tahun 2011 Tentang Otoritas Jasa Keuangan - Evania Larisa; Yoan Nursari Simanjuntak; Yusrambono (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2023)
Insurance plays an important role in human life, as the development of increasingly complex technology allows the occurrence of accidents to increase as well. The role of insurance is to provide protection against the uncertainty of events that may occur. Insurance customers play an important role in insurance companies. The customer is the main source of financial funds for the insurance company so that the company continues to run well, but in running its business the insurance company does not rule out the possibility of facing an obstacle experiencing a state of default. The default situation will result in losses for insurance customers to get their ongoing and past due claims. Efforts to protect consumers in the financial services sector are carried out by an independent institution whose establishment is based on Law no. 21 of 2011 which is referred to as the Financial Services Authority (OJK). Through the normative juridical research method by conducting a literature study on legal materials, the results obtained that the enactment of the OJK Law shows that the OJK plays a very strategic role in the legal protection of PT. Kresna Life Insurance that has failed to pay. Keywords: Insurance customers; Legal protection; Financial Services Authority (OJK).